The Responses of Germ-Free Zebrafish (Danio rerio) to Varying Bacterial Concentrations, Colonization Time Points, and Exposure Duration - Tan, Fang; Limbu, Samwel Mchele; Qian, Ye; Qiao, Fang; Du, Zhen-Yu; Zhang, Meiling (Frontiers in Microbiology, 2019)
Colonizing germ-free (GF) zebrafish with specific bacterial species provides the possibility of understanding the influence on host biological processes including gene expression, development, immunity, and behavioral responses. It also enlightens our understanding on the host-microbe interactions within the physiological context of a living host. However, the responses of GF zebrafish to various colonization conditions such as bacterial concentrations, colonization time points, and exposure duration remain unclear. To address this issue, we explored the responses of GF zebrafish by using two bacterial species at varying concentrations, colonization time points and exposure duration. Therefore, we mono-associated GF zebrafish with Escherichia coli DH5α or Bacillus subtilis WB800N at concentrations ranging from 102 to 107 CFU/ml either at 3 day post fertilization (dpf) or 5 dpf for 24 or 48 h. We evaluated the responses of GF zebrafish by analyzing the survival rate, colonization efficiency, nutrients metabolism, intestinal cell proliferation, innate immunity, stress, and behavior responses by comparing it to conventionally raised zebrafish (CONR) and GF zebrafish. The results indicated that the final bacteria concentrations ranging from 102 to 104 CFU/ml did not cause any mortality when GF mono-associated larvae were exposed to either E. coli DH5α or B. subtilis WB800N at 3 or 5 dpf, while concentrations ranging from 106 to 107 CFU/ml increased the mortality, particularly for 5 dpf owing to the decrease in dissolved oxygen level. The E. coli DH5α mainly induced the expression of genes related to nutrients metabolism, cell proliferation and immunity, while B. subtilis WB800N mainly upregulated the expression of genes related to immunity and stress responses. Moreover, our data revealed that GF zebrafish showed higher levels of physical activity than CONR and the microbial colonization reduced the hyperactivity of GF zebrafish, suggesting colonization of bacteria affected behavior characteristics. This study provides useful information on bacterial colonization of GF zebrafish and the interaction between the host and microbiota.